Assessing the risk factors and management outcomes of ectopic pregnancy: A retrospective case-control study - Azadeh Tarafdari; Mahin Bandarian; Sedigheh Hantoushzadeh; Alireza Hadizadeh; Saeedeh Shahsavari; Maryam alsadat Razavi (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Ectopic pregnancy (EP) is the implantation of a fertilized egg outside the uterine cavity or in an unusual location. According to the clinical case reports, hormonal contraceptive failures may be related to emergency contraceptives and EP. EP may be treated medically, surgically, or expectantly. Currently, there is no consensus regarding whether a multiple- or double-dose regimen with methotrexate (MTX) or an additional dose could be more effective than a single-dose regimen. Objective: This study aimed to assess risk factors and treatment outcomes for EP. Materials and Methods: This case-control study was conducted in Tehran, Iran from March 2020 to March 2021. The case group was comprised of all EP-diagnosed cases (n = 191). Based on the levels of β-human chorionic gonadotropin, MTX was administered to stable individuals with no surgical indications. Risk factors were assessed through 2 control groups: intrauterine pregnancy (n = 190) and nonpregnant groups (n = 180). Results: The medical treatment significantly improved with an extra dose of MTX, especially in individuals with higher β-human chorionic gonadotropin concentrations and gestational age > 7.5 wk (p = 0.002). Considering risk factors, it is assumed that hormonal contraceptive failures, including both oral and emergency contraceptives, may increase the EP likelihood (p < 0.001). Conclusion: Based on our findings, we recommended an additional dose of MTX for subjects who are further along in their pregnancy. It is also concluded that failure of contraceptive pills increases the chances of EP.